The Identity of the Main Character in Youth Novel "Yildiz heißt Stern" by Isolde Heyne - Okky Dwi Hapitta; Audrey Gabriella Titaley (Nusantara Science and Technology Proceedings)
Life in another country with a different culture can lead to anxious lives, as the Turkish main characters experience in Isolde Heyne's youth novel “Yildiz heißt Stern”. That is what this study is about, and it aims to portray the personal development of the two main characters. For this reason, theories related to identity theory, cultural studies and narratology have been applied. The results of the analysis confirm that the main characters can adapt well within a known radius. Only after the main characters have overcome difficulties in life due to their identity and accepted them do they learn to deal with German culture. At the same time, they can also be influenced personally and culturally by it.